## Expanding (x + 3)²

The expression (x + 3)² represents the square of the binomial (x + 3). To find the answer, we need to expand this expression using the **FOIL method** or by using the **square of a binomial formula**.

### Using the FOIL Method

FOIL stands for **First, Outer, Inner, Last**. This method helps us multiply two binomials systematically:

**First:**Multiply the**first**terms of each binomial: x * x = x²**Outer:**Multiply the**outer**terms of the binomials: x * 3 = 3x**Inner:**Multiply the**inner**terms of the binomials: 3 * x = 3x**Last:**Multiply the**last**terms of each binomial: 3 * 3 = 9

Now, add all the terms together: x² + 3x + 3x + 9

Finally, combine the like terms: **x² + 6x + 9**

### Using the Square of a Binomial Formula

The square of a binomial formula states: **(a + b)² = a² + 2ab + b²**

In our case, a = x and b = 3. Applying the formula:

(x + 3)² = x² + 2(x)(3) + 3²

Simplifying: **x² + 6x + 9**

### Conclusion

Both methods lead to the same answer: **(x + 3)² = x² + 6x + 9**. Expanding the expression reveals the trinomial form which can be useful for various mathematical operations and applications.